Long-Term Trends in the Utilization of Cone Beam Computed Tomography in Oral and Maxillofacial Radiology - Nithin Kumar; Bhavna Malik; Alok Dubey; Harveen Kaur; Sheetal Mujoo; Shraddha C. Jugade; Sunil K. Gulia (Wolters Kluwer Medknow Publications, 2024)
Background: Cone beam computed tomography (CBCT) has become a cornerstone in oral and maxillofacial radiology due to its high-resolution, three-dimensional imaging capabilities and lower radiation exposure compared to traditional computed tomography (CT). The purpose of this retrospective study is to examine long-term patterns in the use of CBCT in a tertiary care context, with an emphasis on patient characteristics, CBCT indications, and variations in use patterns over time. Methods: During the course of 5 years, a tertiary care facility performed 500 CBCT scans, all of which were included in the study. Information on the age, sex, and source of referral for each patient was gathered from their electronic medical records. Radiology data were used to categorize CBCT indications, which included implant planning, impacted tooth assessment, and pathology evaluation. Regression analysis and descriptive statistics were used to examine utilization trends. Results: Throughout the study period, there was a consistent rise in the use of CBCT, with implant planning being the most often cited indication. Impacted tooth assessment and pathology evaluation were next in line. Considerable differences were noted in the use of CBCT for various age groups and indications. The results demonstrate how CBCT is improving oral and maxillofacial radiology's diagnostic precision and treatment planning. In summary, this study offers a significant understanding of the long-term patterns in CBCT use in a tertiary care context. With ramifications for resource allocation, patient care, and future research objectives, the observed trends highlight the increasing acceptability and incorporation of CBCT into standard clinical practice.